Indicators of quality condition of soils as a basis for rational use of land - Tykhenko, O.; Shamchuk, A. (Land Management, Cadastre and Land Monitoring, 2022)
The study of specific indicators of soil cover and their impact on land productivity is an important task for the formation of rational use of land resources. The aim of the work was to assess the condition of soils and find the optimal fertility parameters of a particular soil in the natural agricultural region. This is very important not only for the study of ways of rational land use, but also for ensuring the fiscal purposes of the cadastre, as the main territorial unit of monetary valuation of agricultural land is a natural agricultural region. This study describes the state of soils through the relationship of specific fertility indicators and the corresponding production opportunities for their use in agriculture. Correlation-regression analysis was performed, which showed that minimum tillage is preferred, as it has a moderate, strong and very strong correlation between phosphate and other soil fertility indicators. To assess the various methods of land use, it is necessary to select parameters for assessing the state of land quality. To this aim, a set of parameters of specific soil and their changes under the influence of different technologies for growing crops was analyzed. In particular, the influence of phosphate regime indicators on winter wheat yield was established. Ways of rational land use have been developed on the basis of soil fertility indicators, which are typical for a specific natural-agricultural area.The results of the work can be used in the development of a set of measures for the rational use of land. The prospect of further research is to develop a set of indicators for land quality.Key words: land plots, rational land use, soil, land use, natural agricultural region, land quality.